2018
DOI: 10.1029/2018gc007632
|View full text |Cite
|
Sign up to set email alerts
|

Submarine Deep‐Water Lava Flows at the Base of the Western Galápagos Platform

Abstract: To investigate the initial phases of magmatism at the leading edge of the upwelling mantle plume, we mapped, photographed, and collected samples from two long, deep‐water lava flows located at the western base of the Galápagos Platform using the remotely operated vehicle Hercules. Lavas were recovered from four areas on the seafloor west of Fernandina volcano, including the western flow fronts of two deep‐water flows, heavily sedimented terrain between the two flows, and the eastern, shallower end of one flow.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 71 publications
(196 reference statements)
0
13
0
Order By: Relevance
“…Combined, this suggests that the alkalic magmas bypass Fernandina's present-day shallow magma reservoir. Instead, the seamount alkalic samples are compositionally identical to alkalic deep water lava flows sampled in situ on the seafloor at the leading edge of the Galápagos plume (Figure 5c; Anderson et al, 2018) and similar, but more alkalic than, those sampled to the north at Roca Redonda (Standish et al, 1998).…”
Section: Western Regionmentioning
confidence: 66%
See 4 more Smart Citations
“…Combined, this suggests that the alkalic magmas bypass Fernandina's present-day shallow magma reservoir. Instead, the seamount alkalic samples are compositionally identical to alkalic deep water lava flows sampled in situ on the seafloor at the leading edge of the Galápagos plume (Figure 5c; Anderson et al, 2018) and similar, but more alkalic than, those sampled to the north at Roca Redonda (Standish et al, 1998).…”
Section: Western Regionmentioning
confidence: 66%
“…Only samples reasonably cleaned of alteration were analyzed for major and trace elements (N = 81), and subsequent isotopic analysis (N = 31). The majority of our samples were recovered using the M/V Alucia, but we include in our discussion 13 samples collected on the R/V Nautilus (Anderson et al, 2018;Schwartz et al, 2018b) since three of these samples were analyzed for isotopes and are presented in this study. Trace elements from Schwartz et al (2018b) have been reprocessed using updated standard values and reported here, so they can be compared directly with our data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations